PENGARUH SUASANA TOKO DAN HARGA TERHADAP MINAT BELI KONSUMEN PADA TOKO BOLLY DEPARTEMENT STORE DI KOTA BIMA - Muhajirin Muhajirin; Ismunandar Ismunandar; Kamaluddin Kamaluddin (Jurnal Akrab Juara, 2018)
The purpose of this research is (1) ) To know and analyze the positive and significant influence of shop atmosphere on buying interest at Bolly Department Store in Bima city (2) To know and analyze the positive and significant influence of price on buying interest at Bolly Department Store in Bima city (3) To know and analyze the positive and significant influence of shop atmosphere and price on buying interest at Bolly Department Store in Bima city. The technique of data is analysing multiple regression linear. The results of the research are: (1) shop atmosphere has a negative effect on the buying interest at Bolly Department Store in Bima city (2) Price has a positive and significant effect on the buying interest at Bolly Department Store in Bima city (3) shop atmosphere and Price has a positive and significant effect on the buying interest at Bolly Department Store in Bima city Keyword: shop atmosphere, Price and buying interest